Measuring competence in systemic practice: development of the 'Systemic Family Practice – Systemic Competency Scale' (SPS). Issue 1 (25th October 2018) - Butler, Catherine; Sheils, Elizabeth; Lask, Judith; Joscelyne, Trish; Pote, Helen; Crossley, Jon
Abstract : Ensuring that practitioners are competent in the therapies they deliver is important for training, therapeutic outcomes and ethical practice. The development of the Systemic Practice Scale (SPS) is reported – a measure to assess the competence of students as trialed by Children and Young Person's Improving Access to Psychological Therapies (CYP‐IAPT) training courses. Initial reliability assessment of the SPS with twenty‐eight supervisors of systemic practice evaluating students' competence using an online recording of a family therapy session is detailed. The SPS was found to be a reliable measure of systemic competence across training settings. Rating variability was noted, with training and benchmarking to improve rating consistency recommended. Further research using the SPS to further establish the reliability and validity of the scale is required. Practitioner points: SPS represents an important tool, particularly for the supervision and development of more junior staff or students Initial reliability for use of the SPS as a formative tool has been established. Further benchmarking is required if using the tool in a summative manner 抽象: 测量系统实践中的能力："系统家庭实践—系统能力量表"（SPS）的发展过程 确保从业者能够胜任他们所提供的治疗对于培训、治疗结果和职业伦理都非常重要。本文报告了系统实践量表（SPS）的发展。该量表评估接受了"儿童和青少年改善渠道心理治疗（CYP‐IAPT）"培训课程的学生的能力。本文详细介绍了SPS的初始信度评估，其中包括28名系统实践督导，他们通过一份网上的家庭治疗会谈录音评估学生的能力。研究发现，SPS在不同的培训环境下都能够可靠地衡量系统能力。研究者也注意到评分中的不确定性，因此建议通过培训和基准测试来提高评分一致性。需要进一步在研究中使用SPS来进一步建立量表的信度和效度。 对实务工作者的启示: SPS是一个重要工具，特别是针对更年轻员工或学生的监督和发展方面 SPS作为进展性评估工具的初始信度已建立。如果要以总结性评估的方式使用该工具，则需要进一步的基准测试。 Resumen: Medición de la competencia en la práctica sistémica: desarrollo de la 'Práctica familiar sistémica‐Escala de competencia sistémica' (SPS) Asegurar que los profesionales sean competentes en las terapias que realizan es importante para la formación, para los resultados terapéuticos y también para la ética. Ese artículo presenta el desarrollo de la Escala de Práctica Sistémica (SPS por sus siglas en inglés), una medida para evaluar la competencia de los terapeutas en formación según se comprobó en los cursos de formación del modelo CYP‐IAPT. Se detalla la evaluación inicial de fiabilidad del SPS con veintiocho supervisores de práctica sistémica que evalúan la competencia de los estudiantes utilizando una grabación on‐line de una sesión de terapia familiar. Se encontró que el SPS era una medida confiable de la competencia sistémica en los entornos de capacitación. Se observó la variabilidad de las puntuaciones de competencia halladas, y se recomendó formación y evaluación comparativa para mejorar la consistencia de dichas puntuaciones. Se requieren investigaciones adicionales que utilicen el SPS para establecer aún más la fiabilidad y validez de la escala. Puntos de implicación práctica: SPS representa una herramienta importante, especialmente para la supervisión y el desarrollo de jóvenes terapeutas o bien de terapeutas en formación Se ha establecido la fiabilidad inicial para el uso del SPS como herramienta formativa. Se requiere una evaluación comparativa adicional si se utiliza la herramienta de manera colectiva